Utilization of E-Money in the Academic World - Sander, Alex; Pertiwi, Weni Arma; Heriyanti, Lesti; Wijayanti, Ayu (Jurnal Ilmiah Mandala Education (JIME), 2025)
The rapid digital transformation in higher education has significantly impacted financial transaction systems, with electronic money (e-money) emerging as a pivotal technological innovation. This mixed-methods research comprehensively investigates the utilization, challenges, and implications of digital payment systems within academic institutions. By employing a sophisticated research design that integrates quantitative and qualitative methodologies, the study explores the adoption, user experiences, and technological infrastructure of e-money in higher education settings.The research encompassed a diverse sample of academic stakeholders across multiple universities, utilizing stratified random sampling to ensure representative data collection. Key findings reveal a substantial digital payment adoption rate of 72% among students and 68% among academic staff, indicating a significant shift towards digital financial ecosystems. The study identified critical factors influencing e-money adoption, including system security, user interface design, accessibility, and technological infrastructure.Notably, the research uncovered substantial variations in digital payment adoption based on socioeconomic backgrounds and geographical locations. Transaction efficiency improved by approximately 67%, with payment processes reduced from an average of 15-20 minutes to less than 3 minutes. However, challenges persist, with 33% of respondents reporting technical difficulties and accessibility concerns.The research contributes significant insights into the digital transformation of financial transactions in higher education, highlighting the need for inclusive technological strategies, robust security mechanisms, and continuous user education. Recommendations include enhancing technological infrastructure, developing user-centric design approaches, and fostering collaborative ecosystems between educational institutions, technology providers, and regulators.This study provides a comprehensive framework for understanding the complex dynamics of e-money adoption in academic environments, offering valuable perspectives for policymakers, educational administrators, and technology developers. By examining the intersection of technology, user experience, and institutional practices, the research illuminates the evolving landscape of digital financial systems in higher education.